(untitled) (Journal of Business and Management Research, 2016)
Recent decades have witnessed unprecedented changes in workforce composition, resulting in women’s increased involvement in the labor force. However, the proportion of women employees vary significantly within various organizational levels, with more women confined to junior level positions within organizations. This study, conducted in two phases, explored the career progression barriers as perceived by Nepali women employees to develop a set of 22-items questionnaire which was then used to examine how 114 women employees perceived those barriers in their career in management. Effort was also made to find if the perceived barriers were specific to any sub-group (position, job responsibility, and/or organization type). Findings of the study revealed that societal-related barrier was most prominent within which marriage during prime of career significantly hampered the career development of Nepali women employees. Further analysis indicated that the perceived barriers were not specific to any sub-group. These results have implications for organizations to improve policies and facilities in order to promote women’s career progression. Limitations of the study are identified and suggestions for future results are discussed. Journal of Business and Management Research, Vol. 1 (2), 2016, pp. 17-32